C30 pumping concrete with heat resistance of 700 DEG C and preparation method thereof

CN116675490BActive Publication Date: 2026-10-09SHANGHAI CAIBA TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310582515.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-23
Publication Date
2026-10-09
Estimated Expiration
2043-05-23

AI Technical Summary

Technical Problem

随着施工要求的不断提高,对混凝土的耐热度要求也越来越高,耐500℃高温的混凝土已经无法满足部分建筑的施工要求,现亟需一种耐高温系数更高的混凝土来满足施工要求

Benefits of technology

[0032] (1) The C30 pumpable concrete with a heat resistance of 700℃ of the present invention is formulated with polycarboxylate high-performance admixture and cementitious system, which has good pumpability and solves the problems of pumpability and workability of heat-resistant concrete in engineering applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004242094510000021
    Figure BDA0004242094510000021
  • Figure BDA0004242094510000041
    Figure BDA0004242094510000041
  • Figure BDA0004242094510000051
    Figure BDA0004242094510000051
Patent Text Reader

Abstract

This invention provides a C30 pumpable concrete with a heat resistance of 700℃ and its preparation method, wherein the unit dosage ratio of each component in the concrete (kg / m³) is specified. 3 The following is a mixture of ingredients: cement 140-160g, fly ash 80-100g, slag powder 80-100g, natural fine sand with a fineness modulus of 1.8-2.0 350-400g, basalt manufactured sand 450-500g, 5-25mm continuously graded basalt crushed stone 1000-1040g, admixture 3.0-3.3g, mixing water 150-160g, and polypropylene fiber 0.9g. The resulting concrete has an average strength of 38MPa after 28 days. After drying at 110℃ for 24 hours and then firing at 700℃ for 3 hours, the residual strength is greater than 27MPa. There are no surface cracks. The slump is 180±20mm within 2 hours, and the density is 2350 kg / m³. 3 ~2400kg / m 3 The residual strength of the C30 pumped concrete with a heat resistance of 700℃ produced by this invention is at least 90%, which is far higher than the design standard, and the safety margin for using this type of concrete is high.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of building materials technology, and in particular to a C30 pumpable concrete with a heat resistance of 700℃ and its preparation method. Background Technology

[0002] Concrete is one of the most important civil engineering materials in modern times. It is an artificial stone material made by mixing cementitious materials, granular aggregates (also known as aggregates), water, and, when necessary, admixtures and additives in a certain proportion, uniformly mixing, compacting, and curing. Concrete is characterized by abundant raw materials, low price, and simple production process, leading to its increasing use. Concrete also features high compressive strength, good durability, and a wide range of strength grades. These characteristics make it widely used, not only in various civil engineering projects, but also in shipbuilding, machinery manufacturing, marine development, geothermal engineering, and other fields.

[0003] Heat-resistant concrete refers to special concrete that can maintain its required physical and mechanical properties under long-term exposure to high temperatures ranging from 200℃ to 1300℃. Chinese invention patent No. 201510805432.4 discloses a C40 pumped concrete with a heat resistance of 500℃. The prepared concrete can withstand temperatures up to 500℃ and has higher strength than traditional high-temperature resistant concrete, making it widely applicable in the load-bearing structures of most modern buildings. However, with increasingly stringent construction requirements, the heat resistance of concrete is also demanding higher standards. Concrete with a heat resistance of 500℃ is no longer sufficient for the construction requirements of some buildings, necessitating a concrete with an even higher heat resistance coefficient to meet these requirements. Summary of the Invention

[0004] In view of the shortcomings of the prior art described above, the purpose of this invention is to provide a C30 pumpable concrete with a heat resistance of 700℃, so as to simultaneously meet the requirements of heat resistance, strength, pumpability and large-scale production. At the same time, this invention will also provide a method for preparing C30 pumpable concrete with a heat resistance of 700℃.

[0005] To achieve the above objectives and other related objectives,

[0006] In a first aspect, the present invention provides a C30 pumpable concrete with a heat resistance of 700°C, wherein the unit volume ratio of each component in the concrete is (kg / m³). 3The following are the components: cement 140-160g, fly ash 80-100g, slag powder 80-100g, natural fine sand with a fineness modulus of 1.8-2.0 350-400g, basalt manufactured sand 450-500g, 5-25mm continuously graded basalt crushed stone 1000-1040g, admixture 3.0-3.3g, mixing water 150-160g, and polypropylene fiber 0.9g; the basalt crushed stone and the basalt manufactured sand used have a SiO2 content of 45-53%, a fineness modulus of 2.9-3.2, a powder content ≤1.0%, and a density of 2.8-3.3g / cm³. 3 Apparent density ≥ 2800 kg / m³ 3 The compressive strength is 350–500 MPa; the weight ratio of the fly ash to the slag powder is 1:1 to 1.25:1. The average strength of the prepared concrete after 28 days is 38 MPa. After drying at 110℃ for 24 hours and then burning at 700℃ for 3 hours, the residual strength is greater than 27 MPa. There are no surface cracks. The slump is 180 ± 20 mm within 2 hours, and the density is 2350 kg / m³. 3 ~2400kg / m 3 .

[0007] As a preferred technical solution, the basalt crushed stone has a particle size of 5-25 mm, a mud content of less than 0.5%, and an apparent density of not less than 2850 kg / m³. 3 The porosity is no greater than 38%, and the crushing value is no greater than 4%.

[0008] As a preferred technical solution, the cement is P·II52.5 silicate cement with a 28-day mortar compressive strength ≥58MPa, a standard consistency water content ≤27%, a tricalcium aluminate (C3A) mineral component content ≤5.0%, and a specific surface area ≤380m². 2 / kg.

[0009] As a preferred technical solution, the natural fine sand has a mud content ≤1.0% and an apparent density ≥2580kg / m³. 3 .

[0010] As a preferred technical solution, the slag powder is grade S95, with a flowability ratio ≥105% and 28-day activity ≥100%.

[0011] As a preferred technical solution, the length of the polypropylene fiber is 20-60 mm.

[0012] As a preferred technical solution, the admixture is a polycarboxylate high-performance water-reducing agent with a water reduction rate of 18% to 23% and a slump retention time of ≥2h for concrete.

[0013] A second aspect of the present invention provides a method for preparing C30 pumpable concrete with a heat resistance of 700℃, for preparing the above-mentioned pumpable concrete, comprising the following steps:

[0014] Step 1: Weigh out natural fine sand, basalt manufactured sand, basalt crushed stone, and polypropylene fiber according to the proportions. Put the basalt manufactured sand, basalt crushed stone, and polypropylene fiber into the mixer and pre-mix for 30s to 60s.

[0015] Step 2: Add cement, slag powder, fly ash, admixtures, and water to the mixer according to the proportions and continue mixing for 30 to 60 seconds to obtain concrete;

[0016] Step 3: Load the concrete into a mixer truck, transport it to the construction site, and pump and pour it into shape.

[0017] The industry standard "Technical Specification for Application of Heat-Resistant Concrete YB / T 4252-2011" specifies the residual strength index for the heat resistance performance of concrete as shown in Table 1:

[0018] Table 1

[0019]

[0020] Therefore, the requirements for residual strength differ at temperatures exceeding 500℃ compared to 500℃. This invention increases the high-temperature resistance of concrete from 500℃ to 700℃ by controlling the following four conditions:

[0021] ① The manufactured sand and gravel of andesite were replaced with manufactured sand and gravel of basalt, as shown in Table 2:

[0022] Table 2

[0023] <![CDATA[SiO₂ content / %]]> 45~53 53~66 <![CDATA[density / g / cm 3 > 2.8~3.3 2.4~2.7 Rock compressive strength / MPa 350~500 100~200

[0024] Because andesite has a higher SiO2 content than basalt, its coefficient of thermal expansion is closer to that of cementitious materials such as cement. Therefore, andesite can be used in concrete mixes with higher cementitious material ratios, while basalt cannot. Thus, the total amount of cementitious material in the experiment must be controlled to not exceed 360 kg / m³. 3 Therefore, the strength grade should not be too high; at the same time, since basalt has a high density, its usage should be increased in order to achieve the required volume of concrete mix proportions, which also increases the volume stability of concrete; and since the compressive strength of basalt is about 1.75 to 2.5 times that of andesite, after being subjected to a high temperature of 700℃, the residual strength of basalt concrete is 40% higher than that of concrete using andesite.

[0025] ② The amount of cement and other cementitious materials used was reduced, and the strength grade of the concrete was lowered;

[0026] Because cement, mineral powder, and fly ash expand significantly under high temperatures, this expansion can potentially lead to structural damage (especially when their expansion coefficients differ from those of aggregates). Simultaneously, higher cementitious material content leads to a substantial increase in concrete density, making it difficult for excess moisture within the hardened concrete to dissipate. Since moisture also expands and causes damage under high temperatures, it is necessary to reduce the amount of cementitious material and the concrete strength grade for high-temperature resistant concrete, especially concrete with a heat resistance of 700℃ (concrete density and strength grade are generally positively correlated). Therefore, to meet the 700℃ heat resistance requirement, the total amount of cementitious material and the concrete strength grade in the mix design were adjusted.

[0027] ③Further reduced water consumption;

[0028] Water is essential for concrete production, but one of the main reasons for the thermal damage to concrete is the evaporation and expansion of free water within the concrete, which leads to internal structural damage. Therefore, reducing water consumption and decreasing the amount of free water in the internal pores of concrete is also an important measure to reduce concrete damage.

[0029] ④ The fiber length was increased, and the fiber-enhanced concrete admixture process was improved to ensure the uniformity of the fiber in the concrete.

[0030] In previous tests of heat-resistant concrete, excessively long fibers led to a decrease in the concrete's strength, workability, and heat resistance. This was mainly because longer fibers were difficult to disperse, resulting in partial aggregation and potentially creating connections between large defects within the concrete. After the fibers melted, the concrete's heat resistance decreased, and in severe cases, it could cause overall spalling and other problems. However, through subsequent experimental research and improvements to the production process, the problem of long fiber dispersion was effectively solved by allowing the fibers to be mixed with aggregates for a period of time, thereby improving the heat resistance of the concrete.

[0031] As described above, the complete invention title has the following beneficial effects:

[0032] (1) The C30 pumpable concrete with a heat resistance of 700℃ of the present invention is formulated with polycarboxylate high-performance admixture and cementitious system, which has good pumpability and solves the problems of pumpability and workability of heat-resistant concrete in engineering applications.

[0033] (2) The C30 pumped concrete with a heat resistance of 700℃ of the present invention has a more stable source of raw materials, especially coarse and fine aggregates, than existing heat-resistant concrete, and can be produced and sold on a large scale by mixing plants as commercial concrete.

[0034] (3) The residual strength of the C30 pumped concrete with a heat resistance of 700℃ is at least 90%, which is 2.57 times the residual strength index required by the standard and far exceeds the design standard. The safety margin of this type of concrete is high. Detailed Implementation

[0035] The following specific embodiments illustrate the implementation of the present invention. Those skilled in the art can easily understand other advantages and effects of the present invention from the content disclosed in this specification.

[0036] This invention provides a C30 pumpable concrete with a heat resistance of 700℃, and the unit dosage ratio of each component in the concrete (kg / m³) 3 The following are the components: cement 140-160g, fly ash 80-100g, slag powder 80-100g, natural fine sand with a fineness modulus of 1.8-2.0 350-400g, basalt manufactured sand 450-500g, 5-25mm continuously graded basalt crushed stone 1000-1040g, admixture 3.0-3.3g, mixing water 150-160g, and polypropylene fiber 0.9g; the basalt crushed stone and the basalt manufactured sand used have a SiO2 content of 45-53%, a fineness modulus of 2.9-3.2, a powder content ≤1.0%, and a density of 2.8-3.3g / cm³. 3 Apparent density ≥ 2800 kg / m³ 3 The compressive strength is 350–500 MPa; the weight ratio of the fly ash to the slag powder is 1:1 to 1.25:1. The average strength of the prepared concrete after 28 days is 38 MPa. After drying at 110℃ for 24 hours and then burning at 700℃ for 3 hours, the residual strength is greater than 27 MPa. There are no surface cracks. The slump is 180 ± 20 mm within 2 hours, and the density is 2350 kg / m³. 3 ~2400kg / m 3 .

[0037] The present invention will now be described in detail with reference to specific embodiments:

[0038] Example 1

[0039] This embodiment provides a C30 pumpable concrete with a heat resistance of 700℃, and the unit dosage ratio of each component (kg / m³). 3 )as follows:

[0040] Table 3

[0041]

[0042] Under the above proportions, production shall be carried out according to the following preparation method:

[0043] First, measure out yellow sand, basalt manufactured sand, and basalt crushed stone according to the proportions. Then, put the yellow sand, basalt manufactured sand, and basalt crushed stone into the mixer and pre-mix for 30 seconds. Next, add cement, slag powder, fly ash, polycarboxylate-based high-performance water-reducing agent, and water into the mixer and continue mixing for 30 seconds to obtain heat-resistant concrete. Load the concrete into a mixer truck, transport it to the construction site, and pump it to form the final product.

[0044] The initial slump of the prepared concrete at the factory was 195 mm, and the slump after 2 hours was 175 mm. The density of the hardened concrete was 2360 kg / m³. 3 The concrete compressive strength after 28 days was 37.2 MPa. After drying at 110℃ for 24 hours and then burning at 700℃ for 3 hours, the strength was 33.1 MPa (reaching 110.4% of C30), and there were no cracks on the surface.

[0045] To verify the effect of concrete strength on thermal expansion, residual strength tests were conducted on basalt concrete C30 and C40 after being fired at 700℃ for 3 hours, as shown in Table 4.

[0046] Table 4

[0047]

[0048] The preparation method of the above concrete is roughly the same as that in Example 1, the difference being that the fibers are not pretreated and are mixed together with other raw materials. The test results are shown in Table 5.

[0049] Table 5

[0050] Comparative Example 1 200mm 180mm 37.8MPa 28.7 MPa (95.8%) Microcracks Comparative Example 2 210mm 195mm 52.3MPa 36.0 MPa (90.1%) There are long cracks

[0051] The test results above show that, due to the higher amount of cementitious material in C40 concrete compared to C30 concrete, the residual strength of C40 concrete is lower than that of C30 concrete under the influence of thermal expansion. At the same time, the cracks are more obvious in C40 concrete than in C30 concrete after high-temperature treatment.

[0052] To verify the influence of andesite and basalt on the residual strength of concrete, residual strength tests were conducted on andesite and basalt after being calcined at 700℃ for 3 hours, as shown in Table 6:

[0053] Table 6

[0054]

[0055] The preparation method of the above concrete is roughly the same as that in Example 1, the difference being that the fibers are not pretreated and are mixed together with other raw materials. The test results are shown in Table 7.

[0056] Table 7

[0057]

[0058]

[0059] The test results above show that, although the concrete made with andesite and the concrete made with basalt are basically the same in terms of performance in all aspects, the residual strength of the concrete made with andesite is only 56.4% after being burned at 700℃ for 3 hours, which is 39.4% lower than that of the concrete made with basalt. Therefore, when producing C30 concrete with a heat resistance of 700℃, the concrete made with basalt has a more ideal heat resistance.

[0060] To verify the influence of fiber length and production process on the performance of heat-resistant concrete, polypropylene fibers with lengths of 19 mm and 60 mm were selected. The production processes were as follows: untreated fibers were mixed with other raw materials, and pretreated fibers were mixed with sand and gravel for 30 seconds before adding the remaining raw materials and mixing, as shown in Table 8.

[0061] Table 8

[0062]

[0063] The preparation processes of Comparative Examples 1 and 5 differ from those of Examples 1 and 4 in that premixing is not performed. The experimental results are shown in Table 9.

[0064] Table 9

[0065] Comparative Example 1 200mm 180mm 37.8MPa 28.7 MPa (95.8%) Microcracks Comparative Example 4 200mm 185mm 38.3MPa 32.0 MPa (106.7%) No cracks Comparative Example 5 180mm 140mm 35.4MPa 25.5 MPa (85.1%) There are long cracks Example 1 195mm 175mm 37.2MPa 33.1 MPa (110.4%) No cracks

[0066] The test results above show that different fiber lengths and production processes have significant effects on the heat resistance of concrete. Compared to pre-mixed aggregates, pre-mixed concrete not only has higher strength and residual strength, and better surface condition, but this difference increases significantly with fiber length. This is mainly because pre-mixed fibers have better dispersion properties, resulting in a more uniform distribution within the concrete and better facilitating internal pressure release. This effect is further enhanced by increasing fiber length.

[0067] However, if the fibers are not evenly dispersed and become enriched, they become a defect inside the concrete, causing a decline in various performance indicators. Increasing the fiber length further worsens its dispersion performance, making it even more prone to internal defects. This highlights the importance of pre-treating the fibers with aggregates. Therefore, pre-dispersion treatment of fibers and increasing fiber length are crucial for improving the heat resistance of concrete.

[0068] Extensive testing has demonstrated that the C30 pumpable concrete with a heat resistance of 700℃ and its preparation method of this invention achieve a reasonable combination of concrete components. This not only solves the raw material problem but also enables the large-scale production and application of C30 pumpable concrete with a heat resistance of 700℃ in batching plants, thereby expanding the application range of heat-resistant concrete.

[0069] The above embodiments are merely illustrative of the principles and effects of the present invention and are not intended to limit the invention. Any person skilled in the art can modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by those skilled in the art without departing from the spirit and technical concept disclosed in the present invention should still be covered by the claims of the present invention.

Claims

1. A C30 pumpable concrete with a heat resistance of 700℃, characterized in that, The unit dosage of each component in this concrete is as follows: cement 140~160kg / m³ 3 Fly ash 80~100kg / m³ 3 Slag powder 80~100kg / m³ 3 350-400 kg / m³ of natural fine sand with a fineness modulus of 1.8-2.

0. 3 Basalt manufactured sand 450~500kg / m³ 3 5~25mm continuously graded basalt crushed stone 1000~1040kg / m³ 3 Admixture 3.0~3.3kg / m³ 3 Mixing water 150~160kg / m 3 Polypropylene fiber 0.9kg / m 3 The basalt crushed stone and the basalt manufactured sand used have a SiO2 content of 45-53%, a fineness modulus of 2.9-3.2, a powder content of ≤1.0%, and a density of 2.8-3.3 g / cm³. 3 Apparent density ≥ 2800 kg / m³ 3 The compressive strength is 350~500 MPa; the weight ratio of fly ash to slag powder is 1:1~1.25:

1. The average strength of the prepared concrete after 28 days is 38 MPa. After drying at 110℃ for 24 hours and then burning at 700℃ for 3 hours, the residual strength is greater than 27 MPa. There are no surface cracks. The slump is 180±20 mm within 2 hours, and the density is 2350 kg / m³. 3 ~2400kg / m 3 ; The basalt gravel has a particle size of 5-25 mm, a mud content of less than 0.5%, and an apparent density of not less than 2850 kg / m³. 3 Porosity not greater than 38%, crushing value not greater than 4%; The cement is P·II52.5 silicate cement, with a 28-day mortar compressive strength ≥58MPa, a standard consistency water content ≤27%, a tricalcium aluminate (C3A) mineral content ≤5.0%, and a specific surface area ≤380m². 2 / kg; The length of the polypropylene fiber is 20~60mm.

2. The C30 pumpable concrete with a heat resistance of 700℃ as described in claim 1, characterized in that, The natural fine sand has a mud content of ≤1.0% and an apparent density of ≥2580 kg / m³. 3 .

3. The C30 pumpable concrete with a heat resistance of 700℃ as described in claim 1, characterized in that, The slag powder is grade S95, with a flowability ratio ≥105% and 28-day activity ≥100%.

4. The C30 pumpable concrete with a heat resistance of 700℃ as described in claim 1, characterized in that, The admixture is a polycarboxylate high-performance water-reducing agent with a water reduction rate of 18%~23% and a slump retention time of ≥2h for concrete.

5. A method for preparing C30 pumpable concrete with a heat resistance of 700℃, used to prepare the C30 pumpable concrete according to any one of claims 1-4, characterized in that, Includes the following steps: Step 1: Weigh out natural fine sand, basalt manufactured sand, basalt crushed stone, and polypropylene fiber according to the proportions. Put the basalt manufactured sand, basalt crushed stone, and polypropylene fiber into the mixer and pre-mix for 30s~60s. Step 2: Add cement, slag powder, fly ash, admixtures, and water to the mixer according to the proportions and continue mixing for 30-60 seconds to obtain concrete; Step 3: Load the concrete into a mixer truck, transport it to the construction site, and pump and pour it into shape.

Citation Information

Patent Citations

  • C40 pump concrete with heat resisting temperature of 500 DEG C

    CN105272020A